The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11104-017-3523-3
|View full text |Cite
|
Sign up to set email alerts
|

Rock-type control of Ni, Cr, and Co phytoavailability in ultramafic soils

Abstract: Background and aims Ultramafic soils constitute an extreme environment for plants because of specific physico-chemical properties and the presence of Ni, Cr, and Co. We hypothesized that type of ultramafic parent rock depending on their origin affects the composition of soils and plants. Therefore, phytoavailability of metals would be higher in soil derived from serpentinized peridotite compared to serpentinite because of differences in susceptibility of minerals to weathering. Results Based on DTPA-CaCl 2 ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 78 publications
2
10
0
Order By: Relevance
“…The lack of any depth trend in Ni concentration within the soil profile of Ch3 soils may suggest an internal source of this phenomenon—strong impact of parent material mineralogy (Bonifacio et al 2010). Although nickel-bearing metamorphic rocks occur in numerous sites in SW Poland, and significant enrichment with Ni has been identified in soils directly influenced by these rocks (Kierczak et al 2016; Pędziwiatr et al 2018), the Chernozems under study are not underlain by serpentinites or other ultramafic rocks and do not adjoin known surface outcrops of these rocks. Ni content in these Chernozems is positively correlated with the sand fraction (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of any depth trend in Ni concentration within the soil profile of Ch3 soils may suggest an internal source of this phenomenon—strong impact of parent material mineralogy (Bonifacio et al 2010). Although nickel-bearing metamorphic rocks occur in numerous sites in SW Poland, and significant enrichment with Ni has been identified in soils directly influenced by these rocks (Kierczak et al 2016; Pędziwiatr et al 2018), the Chernozems under study are not underlain by serpentinites or other ultramafic rocks and do not adjoin known surface outcrops of these rocks. Ni content in these Chernozems is positively correlated with the sand fraction (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on serpentinitic and ultramafic soils indicated that the soil properties as well as the variations in PTEs' distribution and bioavailability may be related to the different ultramafic parent rocks (i.e., serpentinites, peridotites, etc.). Most of these studies mainly deal with soil chemistry, metal availability based on chemical extraction procedures, phytoaccumulation investigations, isotopic composition, and pedological characterization (e.g., [23,29,73,[75][76][77][78][79][80]). Only a few studies dealt with the implication of the different ultramafic parent rocks on the development of ultramafic soils and ecosystems, which is particularly important in young and poorly developed soil profiles (e.g., [9,28]).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, although ultramafic soils are commonly grouped together under the term "serpentine soils" [22], significant differences can be present in soils derived from non-or slightly-serpentinized peridotites, massive serpentinites, metamorphic serpentine schists, and fractured or veined serpentinites. These differences can affect the soil chroma, depth, and weathering intensity as well as the nature and relative abundance of primary residual minerals and newly formed authigenic phases [1,15,22,23,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a strong correlation between the Cr and Ni concentrations (correlation coefficient of 0.76) (Table 2), which is indicative that both elements coexisted in the study area and that both could be derived from serpentinite that is rich in Cr and Ni. There are, thus, 2 possible reasons for the coexistence of Cr and Ni: first, 1 of the major outcrops of the study area is the Walash Group, which is rich in Ni and Cr (Al-Bassam, 2008), and second, serpentinite is found in the study area (Morrison et al, 2015 andPędziwiatr et al, 2018).…”
Section: Discussionmentioning
confidence: 99%